Jamaica : Fourth Review Under the Stand-By Arrangement, Request for Modification of Performance Criteria, and Monetary Policy Consultation Clause-Press Release; Staff Report; and Statement by the Executive Director for Jamaica. (IMF Staff Country Reports; Country Report ;, 2018)
Stable macroeconomy but growth continues to underperform. After nearly six years of economic reforms, unemployment is at an almost 11-year low, poverty is at a 9-year low, inflation is low, public debt is firmly on a downward trajectory, and international reserves are at historically high levels. Still, growth remains lackluster. Private investment has not fully taken advantage of the unprecedented opportunities presented by macroeconomic stability and strong fundamentals. Structural impediments need to be quickly addressed to foster capital formation. Sustained weak growth risks impeding reform momentum and could make achieving the government's policy objectives more difficult.